1995
DOI: 10.1002/eji.1830250547
|View full text |Cite
|
Sign up to set email alerts
|

Antigen detection in vivo after immunization with different presentation forms of rabies virus antigen: involvement of marginal metallophilic macrophages in the uptake of immune‐stimulating complexes

Abstract: Several mechanisms have been postulated to explain the relatively high immunogenicity of antigens presented in immune-stimulating complexes (iscom). Their potency can in part be explained by the specific targeting of these structures to cells presenting antigens to the immune system. However, until now no method for the subcellular detection of iscom in situ was available. In the present study, a novel, fast and simple method for the detection of iscoms in situ is demonstrated. By making use of the lipophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Nevertheless, ISCOMS containing the enzymatically inactive CTA1R7K-OVAp-DD molecule induced some responses, supporting previous suggestions that ISCOMS containing peptides can induce humoral immunity in vivo (23). However, this work used much higher doses and larger peptides than in our experiments, indicating that the immunogenicity of ISCOMS may be enhanced by the DD fragment, perhaps because the combined vector can interact with B cells as well as the DC and/or macrophages targeted by conventional ISCOMS (12)(13)(14)24). In addition to targeting different APC, the CTA1-DD-ISCOMS vector contains two active adjuvants, Quil A and the ADP-ribosylating enzyme CTA1, which may have additive effects.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, ISCOMS containing the enzymatically inactive CTA1R7K-OVAp-DD molecule induced some responses, supporting previous suggestions that ISCOMS containing peptides can induce humoral immunity in vivo (23). However, this work used much higher doses and larger peptides than in our experiments, indicating that the immunogenicity of ISCOMS may be enhanced by the DD fragment, perhaps because the combined vector can interact with B cells as well as the DC and/or macrophages targeted by conventional ISCOMS (12)(13)(14)24). In addition to targeting different APC, the CTA1-DD-ISCOMS vector contains two active adjuvants, Quil A and the ADP-ribosylating enzyme CTA1, which may have additive effects.…”
Section: Discussionsupporting
confidence: 88%
“…ISCOMS induce strong T cell-mediated immune responses that include Th1-dependent delayed type hypersensitivity (DTH) and cytokine production, as well as very strong MHC class I-restricted CD8 ϩ T cell responses (10), but CT is a stronger promoter of mucosal IgA and serum Ab responses (10). The complimentary effects of CT and ISCOMS on the immune system are consistent with our own and other findings that whereas B lymphocytes are important for the adjuvant effects of CT and CTA1-DD (8,9,11), ISCOMS are targeted to and activate macrophages and dendritic cells (DC) (12)(13)(14)(15). In parallel, the mucosal adjuvant effects of CT are dependent on IL-4, but not on IL-12.…”
supporting
confidence: 87%
“…Using electron microscopy, Watson et al [71] observed influenzaISCOMs adhered to macrophage cell membranes or contained within phagolysosomes only 30 s after intraperitoneal injection. In a related study, ISCOMs containing rabies virus antigen were labeled with lipophilic fluorescent carbocyanine and their cellular distribution examined after intraperitoneal or intravenous injection [78]. Both rabies antigen and rabies-ISCOMs localized to marginal zone macrophages but the ISCOMs preferentially located to marginal metallophilic macrophages.…”
Section: Uptake and Presentation Of Iscomsmentioning
confidence: 99%
“…1A). Within the splenic marginal zone three different populations of macrophages positive for ER-TR9, MOMA-1, and 2F8 were previously described, organized in rings, where MOMA-1 + macrophages are located close to the white pulp within the marginal zone, surrounded by ER-TR9 + -and 2F8 + macrophages on the outside [4,[9][10][11][12][13][14]. Of the different macrophage subsets resident in the marginal zone 2F8 + scavenger receptor macrophages bound FITC-labeled LPS and no difference could be found between sIgM-deficient and WT mice ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The marginal zone contains B cells flanking the marginal sinus and different subpopulations of highly phagocytic macrophages that are very effective in capturing immune complexes from the passing bloodstream. The outer population of marginal zone macrophages of the spleen express scavenger receptors (2F8) on the surface and is loosely organized, while the inner ring of marginal zone metallophilic (MOMA-1) macrophages, at the border to the white pulp, is tightly structured [8][9][10][11]. In this particular environment, marginal zone CD21 + CD35 + CD19 + IgM + B cells can produce IgM locally and after stimulation marginal zone B cells can proliferate and differentiate to IgM-producing plasma cells [12].…”
Section: Introductionmentioning
confidence: 99%